Comparing the Quality of Life Between Active and Non-Active Elderly Women With an Emphasis on Physical Activity - Mojtaba Ahmadi; Mohammadali Noudehi; Mohsen Esmaeili; Ali Sadrollahi (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Among different people, especially the elderly who are undergoing their specific physical, emotional, and psychological conditions, quality of life is considered an issue that is of paramount importance. The present study aims to make a comparison between the quality of life in elderly women who lead an active life with those with a non-active one with special emphasis on physical activity. Methods & Materials The study is a descriptive research including a sample population of 176 elderly women over 60 years old in Bandar-e Gaz city in Iran. Convenience sampling was performed. To obtain the required data, a Short Form-36 (SF-36) questionnaire was used. For statistical analysis, Kolmogorov-Smirnov (K-S) test and Mann–Whitney U test were used. All the statistical operations were done using SPSS Statistics 20 in significance level of P≤0.05.    Results The results of study indicate that the average age of active and non-active women were 65.69±5.45 and 64.32±5.14 respectively. The active elderly women enjoyed a higher quality of life than the non-active ones considering indicators such as physical performance limitations, physical and emotional problems, and pain and public health. However, in terms of social function indicator, no significant difference was noted between them. Mental and public health indicators are considered as the most important aspects of quality of life. Conclusion The findings of this study suggested engaging in regular physical activity as it could work as a significant strategy to improve the quality of life among the elderly. Therefore, it is strongly recommended that the officials dealing with public health create appropriate facilities for  the physical activity and sports of the elderly women.